ANALISIS PENGARUH MARKETING MIX 4P TERHADAP KEPUTUSAN PEMBELIAN PADA USAHA BUDIDAYA IKAN LELE - Ashari, Azfa Dzalifah; Kusumaningtyas, Dian (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to describe the effect of product quality, price, place, and promotion on purchasing decisions in catfish farming in Muneng. The definition of the problem in this study is how the impact of product quality, price, place, and promotion on purchasing decisions. The systemic methodology in this study uses a quantitative strategy with a causal assessment procedure technique. The population of this study were catfish buyers in the catfish farming business in Muneng Village. The sampling technique used accidental sampling with 100 respondents considering the unlimited number of individuals. Information investigation method using multiple linear regression analysis examination. The test results can be said that product quality influences purchasing decisions, price influences purchasing decisions, places influences purchasing decisions, promotions influence purchasing decisions, and product quality, price, place, and promotion side by side influence purchasing decisions in catfish farming business in Muneng Village.